Pengaruh Pelatihan, Motivasi Kerja Dan Kepuasan Kerja Terhadap Kinerja Karyawan Di Perumda Air Minum Tugu Tirta Kota Malang - Afrillianti, Dyva Aulia; Basalamah, Muhammad Ridwan; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research aims to determine the influence of Training, Motivation and Job Satisfaction on Employee Performance at PDAM Malang City. In this research, the population was 241 employees. Therefore, this study used the Slovin formula to determine the sample size, obtaining results of 73 respondents. This research uses primary data and the data collection method used is an online questionnaire (Google Form). For data analysis, Version 25 software is used to analyze instrument tests, classical assumption tests, multiple linear tests, and hypothesis tests. The results of this research show that the training variable influences employee performance at PDAM Malang City. The motivation variable has no effect on employee performance at PDAM Malang City. Satisfaction has a significant effect on employee performance in Malang City. Keywords: Training, Motivation, Satisfaction, Employee Performance